Alveolar bone regeneration using a 3D‐printed patient‐specific resorbable scaffold for dental implant placement: A case report - Ivanovski, Sašo; Staples, Reuben; Arora, Himanshu; Vaquette, Cedryck; Alayan, Jamil (Clinical oral implants research, 2024)
Background This case report demonstrates the effective clinical application of a 3D‐printed, patient‐specific polycaprolactone (PCL) resorbable scaffold for staged alveolar bone augmentation. Objective To evaluate the effectiveness of a 3D‐printed PCL scaffold in facilitating alveolar bone regeneration and subsequent dental implant placement. Materials and Methods A 46‐year‐old man with a missing tooth (11) underwent staged alveolar bone augmentation using a patient‐specific PCL scaffold. Volumetric bone gain and implant stability were assessed. Histological analysis was conducted to evaluate new bone formation and graft integration. Results The novel approach resulted in a volumetric bone gain of 364.69 ± 2.53 mm3, sufficient to reconstruct the original alveolar bone contour and permit dental implant placement. Histological analysis showed new bone presence and successful graft integration across all defect zones (coronal, medial, and apical), with continuous new bone formation around and between graft particles. The dental implant achieved primary stability at 35 Ncm−1, indicating the scaffold's effectiveness in promoting bone regeneration and supporting implant therapy. The post‐grafting planned implant position deviated overall by 2.4° compared with the initial restoratively driven implant plan pre‐bone augmentation surgery. The patient reported low average daily pain during the first 48 h and no pain from Day 3. Conclusions This proof‐of‐concept underscores the potential of 3D‐printed scaffolds in personalized dental reconstruction and alveolar bone regeneration. It marks a significant step forward in integrating additive manufacturing technologies into clinical practice through a scaffold‐guided bone regeneration (SGBR) approach. The trial was registered with the Australian New Zealand Clinical Trials Registry (ACTRN12622000118707p).